Industrial application of natural fibres : structure, properties, and technical applications - Mussig, Jorg (Wiley series in renewable resources, 2010)
In recent years natural fibers have become increasingly popular for use in industrial applications as reinforcement for plastics. This essential resource brings detailed information on natural fibers from agriculture to the final product